MENANGANI TANTANGAN MANAJEMEN SDM JARAK JAUH DI KOMUNITAS: TANGGAPAN HRD MELALUI KOMUNIKASI - Hanifah, Rafidah Shabrina; Sukmayadi, Vidi; Praja, Wina Nurhayati (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Remote work introduces complex challenges for employees and HRD, especially in communities driven by voluntary participation and superficial interest. Unlike other formal organizations, which have clear, measurable, and definite objectives, communities depend heavily on individual motivation, which is prone to fluctuation. Miscommunication, fluctuations in participation, and digital fatigue threaten individual productivity, requiring proactive HRD responses. This study explores the challenges of managing remote human resources in communities and how HRD responds to maintain engagement and performance. Conducted on Novo Club Batch 2, the study uses a qualitative case study approach. Data were gathered through observation, in-depth interviews with eight informants, and document analysis. The results show that Novo faces structural, participatory, and communication challenges with HRD responses ranging from reactive to adaptive. Viewed through Buhman’s communication strategy cycle, these insights underscore the importance of continuous adaptation in community-based HR management. Additionally, the principles of Strategic Human Resource Management (SHRM) and the 7C of communication serve as supporting lenses to understand how HRD responses can be aligned and delivered effectively. This study sheds light on HRD responses in this context and calls for further investigation into adaptive strategies that can strengthen remote management practices.